Technical visit to KVMRT Line 2 - V207 mined tunnel site - Rini Asnida, Abdullah, Ir. Dr. (The Institution of Engineers, Malaysia (IEM), 2019)
Link to publisher’s homepage at https://www.myiem.org.my/